Pengaruh Partisipasi Penyusunan Anggaran, Kejelasan Sasaran Anggaran Dan Struktur Desentraliasasi Kinerja Manajerial SKPD Lombok Barat - Juaini, Ahmad; Herwanti, Titiek; Furkan, Lalu M. (E-Jurnal Akuntansi; Vol 29 No 2 (2019)DO - 10.24843/EJA.2019.v29.i02.p13, 2019)
This study aims to examine and find empirical evidence regarding the effect of budgetary participation, clarity of budget targets and decentralized structures on the performance of SKPD Management. The number of samples was 126 respondents from 42 SKPD. The analytical tool used in this study is multiple linear regression, the unit of analysis in this study is the Regional Level Work Unit (SKPD) in the West Lombok Regency Government. Research results (1) Clarity of budgetary budget has a significant positive effect on SKPD managerial performance. (2) Budget participation does not affect the SKPD managerial performance. (3) The decentralization structure does not affect the SKPD managerial performance. Keywords :  Budget Participation; Clarity of Budget Goals; Decentralized Structure.